2000
DOI: 10.1038/sj.bmt.1702466
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac systolic function before and after hematopoietic stem cell transplantation

Abstract: Summary:In order to examine the effect of hematopoietic stem cell transplantation (HSCT) on cardiac systolic function, we measured left ventricular ejection fraction (LVEF) by radioventriculography (RVG) before and after the transplantation procedure. One hundred and fortyeight patients were examined, 96 undergoing allogeneic grafting and 52 autologous. Fifty patients had CML, 48 AML, 21 ALL, 18 multiple myeloma and 11 breast cancer. The second RVG examination was performed 22 to 227 days (median 60 days) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 25 publications
(25 reference statements)
0
36
0
1
Order By: Relevance
“…In at least seven studies, LVEF measured at rest was unable to predict future cardiac toxicity. 17,28,79,80,100,104,105 One of these studies also showed that measurement of cardiac reserve during exercise could not predict cardiac morbidity or mortality. 104 On the other hand, three studies reported a significant association between pre-transplant LVEF and cardiotoxicity 18,54,77 and two more described a trend in the same direction.…”
Section: Predictive Value Of Pre-hd Chemotherapy Cardiologic Evaluatimentioning
confidence: 99%
See 3 more Smart Citations
“…In at least seven studies, LVEF measured at rest was unable to predict future cardiac toxicity. 17,28,79,80,100,104,105 One of these studies also showed that measurement of cardiac reserve during exercise could not predict cardiac morbidity or mortality. 104 On the other hand, three studies reported a significant association between pre-transplant LVEF and cardiotoxicity 18,54,77 and two more described a trend in the same direction.…”
Section: Predictive Value Of Pre-hd Chemotherapy Cardiologic Evaluatimentioning
confidence: 99%
“…8,10,17,18,26,[76][77][78][79] On the other hand, Steinherz et al 22 observed that HD cyclophosphamide-associated cardiac damage was most frequent in pediatric patients receiving cyclophosphamide X170 mg/kg or in those receiving X120 mg/kg who had received X100 mg/m 2 anthracyclines prior to transplant. Other authors found a trend towards significance also.…”
Section: Previous Anthracycline Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, our patient was not treated with anthracyclines and showed a preserved ejection fraction before high-dose chemotherapy. Moreover, subsequent studies have shown that both of these conventional markers are insufficient to independently predict the onset of cardiomyopathy (14,15). In a recent report (5), prolongation of corrected QT interval before high-dose CY was strongly associated with the onset of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%